ANALISA JARINGAN PIPA DISTRIBUSI AIR BERSIH PADA KECAMATAN MUARA KAMAN KABUPATEN KUTAI KARTANEGARA - FIRMAN, LA ODE (KURVA S JURNAL MAHASISWA, 2012)
Sub-Province of Kutai kartanegara in this time in general have expanded at full speed, this matter can be seen from some aspect, among others social aspect [of] economics, natural resources and human being, topography and geografi in the year - this year progressively mount referring to its it[him] invite - autonomous invitor [of] area of center. So that area - area more (be) free to in racing development various sector to exploit as good as - its goodness [of] counter balance fund and authority given by central government for the progress of [his/its] area. Policy of central government in carrying out area autonomy [is] in the reality exploited [by] as good as - its goodness by local government of Sub-Province of Kutai Kartanegara to progressively have x'self to order [to] in course of development various sector so that automatically very having an effect on to growth of development and resident Requirement of human being will irrigate cleanness becoming mount, as according to social dynamics [of] society economics and follow resident growth rate. Because with existence of the make-up of clean amount of water required, that goodness for household , industrial, effort shop and also other publik utulities, hence timbulah of[is effort - effort to [be] is ready [of] up to standard clean water either from facet of[is quality of and also quantity. To reach the the effort hence require to be realized by way of planning Clean Distribution Water network system. Basically this distribution [is] meant to fulfill healthy clean amount of water required as according to clean water standard which have been specified, which is on finally aim to also to increase prosperity and health of society, especially related to environmental condition balance With growth of civilization and also progressively increasing [him/ it] of[is amount of resident [in] Kec. Estuary of Kaman, Kab. Kutai Kartanegara, by itself add immeasurable life aktifitas. Previously local society more tend to to living river ditepian of mahakam because them swimmingly get water [at] river of Mahakam, however because growth of resident which progressively increase accompanied.